Establishing Carex scopluorum seedlings to restore the vegetation of Tuolumne Meadows, Yosemite National Park, USA - Booher, Melissa, author; Cooper, David, advisor; Ocheltree, Troy, committee member; Rocca, Monique, committee member (Colorado State University. Libraries, 2018)
Wet meadows are critically altered and at-risk ecosystems globally and in the Sierra Nevada of California. The low vegetation cover created by legacy disturbances is a restoration priority due to the importance of organic-rich soils for future plant establishment, carbon storage, and water retention. Wet meadows are characterized by seasonally saturated fine-textured mineral soils with significantly more organic matter than surrounding areas, shallow groundwater (< 1 m), and vegetation dominated by herbaceous plant species. This research focused on the establishment requirements of seedlings of the native sedge Carex scopulorum in Tuolumne Meadows, Yosemite National Park, USA. I provide critical information on biomass contribution of a key wet meadow species that could also be used in other restoration efforts in similarly degraded subalpine meadows. We tested the suitability of this species for use in future restoration work and assessed the growth of C. scopulorum seedlings in a fully factorial experiment with small mammal herbivore exclosures and planting density treatments. Seedlings were planted in June 2016 and survival was high, approximately 98%, living through the summer of 2016 and 71% surviving through the end of the 2017 summer. After two seasons of growth, planted seedlings more than doubled in area (horizontal tiller spread) and nearly doubled their longest leaf lengths. Total C. scopulorum seedling biomass increased more than six-fold from the delivered seedlings in 2016 to end of the 2017 growing season. Carex scopulorum seedlings had greater mean biomass, 703.44 g/m2 ± 246.54, than all other species in our study plots and had more than twice the belowground biomass per unit area of other herbaceous species sampled. In addition, planted C. scopulorum seedlings allocated a greater portion of their biomass below-ground (higher mean ratio) than all herbaceous species (all comparisons p = <0.05) other than Carex subnigricans (p = 0.051). Our results indicate that C. scopulorum is an appropriate species for restoration in Tuolumne Meadows where increasing biomass inputs to the system is a priority and could be a valuable tool for revegetation and restoration of other degraded meadows in the Sierra Nevada.
Keywords: carex scopulorum; Sierra Nevada; Yosemite; restoration; biomass; wet meadow